Reliability of kinematic measurements during treadmill running - Muniz, A.; Britto, P.; Franco, D.; Fontenelle, G.; Limeira, G.; Zylberberg, M.; Gerken, G.; Nadal, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study aimed at determining the within- and between-day reliability of kinematic data during treadmill running. Seventeen young adult male recreational runners were evaluated in a treadmill running test. Nine reflective markers were placed on the right leg and kinematic data were collected twice on the first day (within-day reliability) and once on the second day (between-day).The peak values of the knee flexion, dorsiflexion, plantiflexion and eversion during stance and knee flexion during swing were evaluated. Higher reliability was observed in within-day (ICC > 0.94, lower CV, typical error and limits of agreement) compared to between-day. The eversion presented the lowest ICC (0.79) in between-day and heteroscedastic error in the within-day measurements. The results indicated that evaluated kinematic data were reliable during running in treadmill.